Good half gone - Fisher, Tarryn (Graydon House Books, 2024)
"Iris Walsh saw her twin sister, Piper, get kidnapped--so why does no one believe her? Iris narrowly escaped her pretty, popular twin sister's fate as a teen: kidnapped, trafficked and long gone before the cops agreed to investigate. With no evidence to go on but a few scattered memories, the case quickly goes cold. Now an adult, Iris wants one thing--proof. And if the police still won't help, she'll just have to find it her own way; by interning at the isolated Shoal Island Hospital for the criminally insane, where secrets lurk in the shadows and are kept under lock and key. But Iris soon realizes that something even more sinister is simmering beneath the surface of the Shoal, and that the patients aren't the only ones being observed..."--Provided by publisher.